“Role of Community Engagement Activities towards Developing Human Resource Professionals: An Exploratory Study of Leading Management Institutions of India With Reference to National Education Policy, 2020” (Journal of Pharmaceutical Negative Results, 2023)
The prime aim of Management education is to develop right managers for the National and International Business scene. But it also seems obvious in today`s business industries that a company`s treatment and understanding of its employees is instrumental to its success. It is the need of the hour that the organizations must not forget to inculcate a sense of social consciousness among the employees. The recent B-Schools are trying to teach their students a sense of moral responsibility towards their society and environment keeping in mind today`s business requirement. Socially conscious employees help their respective organizations to build resilient business that foster stronger leadership, cooperative and collaborative attitude and good customer service. This paper will try to highlight the different community engaging activities conducted by reputed management institutions nationwide with a special focus on one particular institution in eastern part of India. Apart from that this paper will also try to pin point the main aim of higher-education according to National Education Policy, 2020 along with the positive impact of these kind of activities upon the budding Human Resource Professionals.